1994
DOI: 10.1002/j.1460-2075.1994.tb06464.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of post-segregational killing: translation of Hok, SrnB and Pnd mRNAs of plasmids R1, F and R483 is activated by 3′-end processing.

Abstract: The gene systems hok/sok of R1, srnB of F and pnd of R483 mediate plasmid maintenance by killing of plasmid‐free segregants. Translation of the very stable mRNAs encoding the killer proteins is regulated by small unstable antisense RNAs. The differential decay rates of the inhibitory antisense RNAs and the mRNAs encoding the killer proteins is the basis for the onset of killer mRNA translation in newborn plasmid‐free segregants and the killing of these cells. We have suggested previously that this requires tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 31 publications
4
81
0
Order By: Relevance
“…Previously, we found that gel-purified truncated hok mRNA was translated efficiently, whereas full-length hok mRNA-1 and -2 were translated poorly (25,26,28). Here we expand our analyses using native RNAs that were not denatured and renatured before being subjected to translation (Fig.…”
Section: Fig 7 Coupled In Vitro Transcription/rnase H Cleavage Assaymentioning
confidence: 88%
See 3 more Smart Citations
“…Previously, we found that gel-purified truncated hok mRNA was translated efficiently, whereas full-length hok mRNA-1 and -2 were translated poorly (25,26,28). Here we expand our analyses using native RNAs that were not denatured and renatured before being subjected to translation (Fig.…”
Section: Fig 7 Coupled In Vitro Transcription/rnase H Cleavage Assaymentioning
confidence: 88%
“…Cleavage patterns were analyzed by primer extension using the hokA primer, 5Ј-GTGGTAGTTTCATGGC, according to Ref. 28.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there has been no mechanism shown to operate in prokaryotes that can remove an antisense RNA from its target (Thisted et al, 1994a). It has been shown that the hok mRNA is specifically cleaved at its 3'-end and that this processing leads to the translational activation of hok mRNA (Thisted et al, 1994a, b ;.…”
Section: Systems In Which the Killer Is A Protein The Synthesis Of Wmentioning
confidence: 99%